Sense and sensibility (Oxford world's classics, ,, 2012)
'Miss Dashwood had a delicate complexion, regular features, and a remarkably pretty figure. Marianne was still handsomer. Her form, though not so correct as her sister's ... was more striking' As the title of Jane Austen's first published novel suggests, the difference between two sisters, Elinor and Marianne Dashwood, lies not only in their appearance but also in their temperament. Yet Sense and Sensibility not only contrasts Elinor's good sense, her readiness to observe social forms and Marianne's impulsive candor, her warm but excessive sensibility; it also highlights their shared predicament in the face of a competitive marriage market. The sisters' parallel experience of love, and its threatened loss, causes both to readjust and question their own values. Jane Austen's satirical powers of observation and expression spare no one in this lively study of the constraints placed on gentry women in the eighteenth century. Ros Ballaster's introduction to this new Penguin Classics edition discusses Sense and Sensibility as domestic drama and as critique of the wider aesthetic, social and political concerns of Romanticism.
Introduction , Chronology , Further Reading , The Novels of Jane Austen / Claire Lamont , Sense and Sensibility , Note on the text , Emendations to the text , Textual variants between first and second editions , Notes.

Wuthering Heights (Oxford world's classics, ,, 2012)
Wuthering Heights tells the story of a romance between two youngsters: Catherine Earnshaw and an orphan boy, Heathcliff. This tale of hauntings, passion and greed remains unsurpassed in its depiction of the dark side of love.With an Afterword by David PinchingDesigned to appeal to the booklover, the Macmillan Collector's Library is a series of beautifully bound gift editions of much loved classic titles. Bound in real cloth, printed on high quality paper, and featuring ribbon markers and gilt edges, Macmillan Collector's Library are books to love and treasure.
Introduction , Note on the text , Select bibliography , A chronology of Emily Bronte , Genealogical table , Wuthering Heights , Appendix 1. Biographical notice of Ellis and Acton Bell , Editor's preface to the new edition , Extract from the prefatory note to "Selections from Poems by Ellis Bell" , Appendix 2. Selected poems by Emily Bronte , Explanatory notes.

The scarlet letter (Classic collection), ,, 2012)
The Scarlet Letter is the story of three New England settlers at odds with the Puritan society in which they live. Roger Chillingworth, an ageing scholar, arrives in New England after two years separation from his wife Hester to find her on trial for adultery. For refusing to reveal her lover's identity, she is condemned to wear a letter °' sewn onto her clothes. Roger resolves to discover and destroy the man who has stolen his honor. For the next seven years the participants in this bizarre love triangle privately suffer the consequences of betrayal, cowardice, and humiliation. Slowly but surely, the need for redemption grows in each as the story hastens towards its dramatic close.
First published in 1850.

Moby Dick, or, The whale (Classic library for children, ,, 2023)
Looking for adventure and a new life, Ishmael, the story's narrator, decides to find work on a whaling boat. On arriving at the Massachusetts harbour to begin his search, the only bed available is already half occupied by a "cannibal" named Queequeg. Although Queequeg has limited English, a friendship forms and the two men sign up for work together aboard the Pequod under the infamous Captain Ahab. Consumed by an insane rage, Captain Ahab has but one purpose in life-- revenge on the great white whale who maimed and disfigured him.

Black Beauty (Mackin classics, ,, 2012)
"Black Beauty is a perennial children's favourite, one which has never been out of print since its publication in 1877. It is a moralistic tale of the life of the horse related in the form of an autobiography, describing the world through the eyes of the creature. In taking this anthropomorphic approach, the author Anna Sewell broke new literary ground and her effective storytelling ability makes it very easy for the reader to accept the premise that a horse is recounting the exploits in the narrative. The gentle thoroughbred, Black Beauty, is raised with care and is treated well until a vicious groom injures him. The damaged horse is then sold to various masters at whose hands he experiences cruelty and neglect. After many unpleasant episodes, including one where he becomes a painfully overworked cab horse in London, Black Beauty finally canters towards a happy ending. Although Anna Sewell's classic is set firmly in the Victorian period, its message is universal and timeless: animals will serve humans well if they are treated with consideration and kindness." --Amazon.
Pt. 1. My early home , The hunt , My breaking in , Birtwick Park , A fair start , Liberty , Ginger , Ginger's story continued , Merrylegs , A talk in the orchard , Plain speaking , A stormy day , The devil's trade mark , James Howard , The old ostler , The fire , John Manly's talk , Going for the doctor , Only ignorance , Joe Green , The parting , Pt. 2. Earlshall , A strike for liberty , The lady Anne , Reuben Smith , How it ended , Ruined, and going down-hill , A job-horse and his drivers , Cockneys , A thief , A humbug , Pt. 3. A horse fair , A London cab horse , An old war horse , Jerry Barker , The Sunday cab , The golden rule , Dolly and a real gentleman , Seedy Sam , Poor Ginger , The butcher , The election , A friend in need , Old captain and his successor , Jerry's new year , Pt. 4. Jakes and the lady , Hard times , Farmer Thoroughgood and his grandson Willie , My last home

The call of the wild and selected stories (Signet classic, ,, 1998)
First published in 1903, The Call of the Wild borught Jack London international acclaim and a readership that would span generations. Stolen from his comfortable California home, Buck -- a powerful half-St. Bernard, half-Scottish sheepdog -- is shipped to the Klondike and pressed into service as a sled dog. So begins an odyssey in which Buck suffers cruelty and neglect, learns the brutal skills of a survivor, finds a gentle master that he can respect and love, then leaves civilization behind to become the legendary leader of a wolf pack--Cover.
The call of the wild , Diable - a dog , An odyssey of the north , To the man on trail , To build a fire , Love of life.